Impact of Environmental Sanitation and Infection Disease as a Determining Stunting Factor for Children - Aprihatin, Yessy; Barlian, Eri; Fatimah, Siti; Yanti, Erpita; Armaita, Armaita (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Stunting is a condition of a toddler where the length of the child is below the standard age of the child. According to the World Health Organization (WHO), Indonesia is among the third countries with the highest prevalence of stunting in the South-East Asia Regional (SEAR) region. In 2015-2017 the average prevalence of stunting toddlers in Indonesia is 36.4% and this prevalence tends to be static. Environmental sanitation and infectious diseases are one of the determinants of stunting in children under five. Poor sanitation will be associated with an increased risk of infectious diseases that can cause stunting of children under five. If this stunting is not handled, it will cause problems for future generations, especially mental development and physical growth will be disrupted, and it will end in poverty and the threat of survival, thus requiring appropriate intervention in its handling.